Acompanhamento nutricional de paciente com mucopolissacaridose tipo 1: um relato de caso clínico - SILVA, Gisele Medeiros da (2023)
Introduction: Mucopolysaccharidosis type I is part of lysosomal storage diseases, due to deficiency of enzymes responsible for the breakdown of glycosaminoglycans / mucopolysaccharides within cells, triggering varied clinical manifestations, with progressive and multisystemic condition. Between 1982 and 2019, 75 cases of MPS were diagnosed in Northern Brazil, 12 of which were MPS type I. Clinical manifestations affect vision, hearing, cause short stature, rough facial features, frequent respiratory infections, airway obstruction aerial, umbilical hernia, skeletal deformities (multiple dysostosis), inadequate or excessive weight gain (risk factor for the development of the metabolic syndrome), and others. The main treatment for the disease is enzyme replacement therapy, which consists of intravenous administration of the deficient enzyme. Objective: To report the importance of nutritional monitoring according to the clinical manifestations of an individual with type I mucopolysaccharidosis. Methodology: This is a case report carried out in 2021, based on consultations and data collection from medical records at a university hospital in Belém / PA, of a patient diagnosed with type I mucopolysaccharidosis; data were obtained to identify the sociodemographic aspects; to identify the clinical history (past and present); assessment of nutritional status through body composition using bioimpedance and anthropometric assessment; assessment of food consumption, collected by 24-hour dietary recall; and biochemical tests of lipidogram, blood count, complementary and specific tests for diagnosis and monitoring of the disease. Results: The patient had a late diagnosis of mucopolysaccharidosis. He also presented several clinical manifestations characteristic of the disease, including all interconnected with the nutritional aspect, in addition to changes in the biochemical exams of lipidogram, blood count and complementary exams; as well as changes in body composition parameters with excess body fat and obesity; inadequacy of micronutrients and low consumption of fruits, vegetables and legumes. Conclusion: It highlights the importance of nutritional monitoring and knowledge of health professionals about the clinical aspects of the disease, improving the identification of signs and symptoms and possible nutritional repercussions. New cohort studies with a larger sample that address the dietary aspects of these patients are also needed.